Preparation, Properties, and Characterization of Polymer Electrolyte Membranes Based on Poly(1-vinyl-1,2,4 triazole) and Poly(styrene sulfonic acid) - Aslan, Ayşe; Sen, Uenal; Bozkurt, Ayhan (Electrochemical Soc Inc, 2009)
A class of polymer electrolyte membranes was produced by the combination of poly(1-vinyl-1,2,4 triazole) (PVTri) and poly(styrene sulfonic acid) (PSSA) at several stoichiometric ratios with respect to the molar ratio of polymer repeating units. PVTri was synthesized by free-radical polymerization of the monomer, 1-vinyl-1,2,4-triazole, and PSSA was produced from polystyrene by direct sulfonation. The proton-exchange reaction, which resulted in complexation between polymers, was illustrated by Fourier transform infrared spectroscopy. Thermogravimetric analysis showed that the membranes are thermally stable up to approximately 250 degrees C. The existence of single glass-transition temperatures of the polymer electrolytes was shown by differential scanning calorimetry. The scanning electron microscopy results also demonstrated the homogeneity of the materials. The electrochemical stability of the materials was studied by cyclic voltammetry. Proton conductivities of the anhydrous samples were measured using impedance spectroscopy. Under an anhydrous state, maximum proton conductivities of PVTriP(SSA)(4) and PVTriP(SSA)(2) membranes were measured as 0.015 at 150 degrees C and 0.033 S/cm at 120 degrees C, respectively. (C) 2009 The Electrochemical Society. [DOI: 10.1149/1.3176878] All rights reserved.
Keywords: Methanol Fuel-Cells; Proton Conducting Membranes; Phosphoric-Acid; Vinylphosphonic Acid; Imidazole; Blends; Nmr; Performance; Exchange